The Influence of Tax Knowledge, Labor Market Considerations, and Perceived Workload on Accounting Students' Interest in a Career in Taxation - Nurhaliza, Nurhaliza; Halimatusyadiah, Halimatusyadiah (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The main goal of this research is to investigate how understanding of tax laws, job market prospects, and workload perceptions affect accounting students' desire to pursue a career in taxation. This study will use a quantitative method to establish correlations, with data being gathered through an internet survey. The target group for this research consists of undergraduate accounting students enrolled in universities within the LL Dikti II region, such as Bangka Belitung University, Bengkulu University, Lampung University, and Sriwijaya University, with a total of 242 participants included in the sample. Variable measurement involves using a scale that ranges from 1 to 5, and the research methodology utilises the Structural Equation Modelling (SEM) technique with the Partial Least Square (PLS) approach in the SmartPLS version 4.0 software. The outcomes revealed that the three variables of taxation knowledge, consideration of the job market, and perceived workload significantly impacted interest in a career in taxation. These results suggest that students' choices to enter the field of taxation are influenced by various factors, including their level of tax knowledge, the availability of job opportunities, and their preparedness for the workload, with the job market being the most influential factor in their decision-making.